"It was a farce": Chilean redemocratization and the late evolution of a politically-conscious diaspora in Vancouver, Canada, 1978–2006. Issue 2 (4th May 2017) - Hoopes, Michael
ABSTRACT: Despite considerable attention given to Chile's cold war diaspora by social scientists and historians, little attention has been given to the eventual decline of the anti-regime solidarity famously cultivated by Chileans in exile. Changes among Chile's Leftist political movements during the country's most recent return to democracy were key to this decline and were deeply felt by a diaspora often intensely supportive of an armed strategy to oust General Augusto Pinochet and hopeful that his replacement would be a government rooted in the socialist ideals they had maintained in exile. For many, exogenous political change was the driving factor behind what scholars have called the "collapse of myths" stage that, beginning in the mid-1980s, produced a departure from the practices and mindsets characteristic of early exile in favor of a more Canada-centric approach to life outside Chile.